The The Correlation Between Occupational Conditions and the Incidence of Acute Respiratory Infections Among Outpatient Workers: A Cross-Sectional Study - Fatihah Rahmat Avicena; Aulia Chairani; Seftiwan Pratami Djasfar; Pritha Maya Savitri; Nunung Hendrawati; Nurlela (Rumah Sakit Penyakit Infeksi Prof Dr. Sulianti Saroso, 2026)
Background: Substandard workplace environmental conditions may increase the risk of Acute Respiratory Infections (ARIs) among healthcare workers. Environmental factors such as temperature, humidity, and ventilation can influence the growth and transmission of respiratory pathogens. This study aimed to analyze the association between environmental conditions and ARI incidence among outpatient healthcare workers in 2025. Methods: A cross-sectional study was conducted using environmental monitoring data on temperature, humidity, and ventilation, along with ARI incidence data obtained from medical records between August and September 2025. Total sampling was applied, involving 85 outpatient healthcare workers. Data were analyzed using univariate and bivariate analyses with the chi-square test. Results: Among the participants, 60 workers (70.6%) experienced ARIs. Inappropriate environmental conditions were identified for temperature among 43 workers (50.6%), humidity among 58 workers (69.7%), and ventilation among 66 workers (77.6%). Bivariate analysis showed a significant association between humidity and ARI incidence (p<0.001), with inappropriate humidity increasing the risk of ARIs sixfold (OR=6.00; 95% CI: 2.16–16.64). No significant associations were found between temperature (p=0.082) or ventilation (p=0.814) and ARI incidence. Conclusion: Humidity was significantly associated with ARI incidence among outpatient healthcare workers. Inappropriate humidity may promote the growth and survival of respiratory pathogens, thereby increasing the risk of infection. In contrast, temperature and ventilation were not significantly associated with ARIs, possibly due to limited environmental variation and the use of air-conditioning systems.